Conceptions of Moroccan secondary school students in relation to the “Integrative Concept” of plate tectonics - Anouar Alami; Radouan Chakour; Sabah Selmaoui; Aâtika Eddif; Hanaa Chalak (International Journal of Evaluation and Research in Education (IJERE), 2022)
The study of learners’ conceptions of geological concepts has been the subject of several studies in the field of earth science didactics. The majority of these studies show that learners have misconceptions that can be an obstacle to learning Earth sciences. The present work aimed to identify the views of second year undergraduate students on plate tectonics to identify some of the barriers to teaching this unifying scientific theory across the different disciplines of the Earth sciences. The data was gathered with questionnaire administered to students in the second year of the Baccalaureate before teaching about plate tectonics. The results of our study confirmed that student learners do indeed have conceptions of plate tectonics and associated phenomena but have great difficulty in mobilizing their knowledge to explain geological phenomena related to plate tectonics. These difficulties may have several origins: the nature of the geological knowledge transposed, and the very limited knowledge of teachers with a bachelor’s degree in Biology.